Pengembangan Multimedia Interaktif Edukasi Internet Sehat Menggunakan Metode Multimedia Development Life Cycle (MDLC) - Ali Ikhwan; Nabila Amanda; Nurhalizah Sinaga; Nabila Rahmadani Batubara (Journal of Society and Scientific Studies, 2026)
This study aims to develop an interactive multimedia application for healthy internet education as an engaging, interactive, and effective learning medium to improve users’ understanding of internet safety and digital ethics. The development process employed the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. During the concept stage, the objectives, target users, and learning materials were determined. The design stage produced storyboards and user interface layouts, while the material collecting stage focused on gathering multimedia assets such as texts, images, icons, and sound effects. All assets were then integrated during the assembly stage using Adobe Flash CS6 supported by ActionScript to manage interactive functions and quiz scoring mechanisms. System evaluation was conducted through alpha testing using the Black Box Testing method and beta testing involving 20 respondents. The alpha testing results indicated that all application features functioned properly without any system errors. Furthermore, beta testing achieved a feasibility score of 94%, which falls into the “Very Good” category. The findings demonstrate that the developed interactive multimedia application is valid and highly suitable as an educational medium for promoting healthy internet usage. The novelty of this research lies in the integration of healthy internet learning materials with an interactive multimedia-based quiz system that encourages active user participation in the learning process. The implications of this study are expected to contribute to the development of more engaging, effective, and adaptive digital learning media in the era of information technology.